The South China Sea dispute: Will it impact Japan's security policy?. (2nd January 2020) - Borah, Ulupi
ABSTRACT: Japan is heavily dependent on the Sea Lanes of Communications (SLOCs) of the South China Sea for its external trade including the critical energy imports from the Persian Gulf region. Any kind of instability or disruption over the contested waters will have an adverse effect on Japan's trade and economy. The increasingly assertive actions of Beijing, especially the military buildup have raised concerns in Tokyo as it might eventually lead to the strategic control of the SLOCs. Thus, developments in the South China Sea are a major reason why Japan has brought about several changes to its defence and security policies. This paper will explore how Chinese assertions in the South China Sea have encouraged Japan to steadily revise its security policies in a more fundamental way since the end of World War II.